Higher Incidence but Similar Outcomes from Bloodstream Infections in People with Type 2 Diabetes Mellitus: A Retrospective Case-Controlled Analysis. (October 2020) - Bryce, A.N.; Phillips, R.; Skittrall, J.P.; Chakera, A.J.; McLoughlin, J.K.; Sargent, C.S.
Abstract: Aims: People with type 2 diabetes mellitus are more susceptible to infections. This study aimed to compare the microbiology, incidence and clinical outcome of bloodstream infections (BSIs) in people with type 2 diabetes and matched controls amongst a cohort of hospital inpatients in the United Kingdom. Methods: A retrospective analysis was conducted on all positive blood cultures obtained over a one-year period, identifying inpatients with type 2 diabetes and BSIs (n = 151). Matched controls were collated from the same cohort. Admission data were obtained from clinical coding. Patient outcomes were analysed in terms of 90-day mortality, length of stay (LOS) and admission rate to high or intensive dependency units (HDU/ICU). Microbial culture and clinical source of infection were compared between groups. Results: Patients with type 2 diabetes comprised 10.6% of admissions but 21.1% (n = 151) of analysed BSIs (OR: 2.27, p < .001). Similar 90-day mortality rates were seen between people with type 2 diabetes (D) and controls (C) (D: 23/151, C: 28/151, p = .54). Mean LOS was also similar (D: 19.8 days, C: 21.1 days p = .62). In both groups, Escherichia coli was the most commonly isolated organism (D: 64/173, C: 55/171) and the urinary tract the most common identified primary site of BSI (D: 47/151, C: 45/151). Conclusions: Whilst inpatients with type 2 diabetes have increased odds of experiencing BSIs, our single-centre study suggests a diagnosis of type 2 diabetes does not necessarily confer a worse outcome. Highlights: Inpatients with type 2 diabetes are at increased odds of bloodstream infections However, they do not experience a worse prognosis from these infections The urinary tract was the most common source and E. coli the most cultured organism Therefore, focus on early prevention and treatment is paramount